Nitrogen-doped carbon electro-Fenton breathing cathode and preparation method and application thereof
By using nitrogen-doped carbon-electrofenton respiration cathode in electrofenton technology, using nitrogen atoms to activate H2O2 to generate·OH, the high aeration cost and metal ion leaching problems in traditional technology are solved, and the effect of efficient degradation of phenol wastewater is achieved. .
Patent Information
- Application Number
- CN202411279429.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Traditional electrofenton technology has problems with high aeration costs and secondary pollution caused by metal ion leaching when degrading phenol wastewater. New electrofenton cathodes need to be developed to save aeration costs and avoid metal ion leaching.
Using nitrogen-doped carbon-electric Fenton respiratory cathode, the surface of the carbon felt substrate is pretreated, and nitrogen-containing precursor substances and graphite dispersion are uniformly applied, and nitrogen-doped carbon is formed by calcination without exogenous metals. The electrode uses nitrogen atoms to activate H2O2 to generate·OH and degrade phenol.
The generation of high-yield H2O2 without aeration is achieved, secondary pollution caused by metal ion leaching is avoided, the removal rate of degraded phenol reaches more than 95%, and the electrode material is highly stable, and the process is clean and pollution-free.
Smart Images

Figure CN119118308A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a nitrogen-doped carbon electro-Fenton breathing cathode and a preparation method and application thereof. Background Art
[0002] Phenol has a stable structure and is not easily degraded. Phenol in the environment can pollute both water and the atmosphere. Untreated phenolic wastewater discharged directly into the water will harm the reproduction and survival of aquatic organisms, and then affect humans. At present, the main treatment methods for removing phenol from wastewater include physical, chemical and biological methods. In recent years, technologies such as adsorption, biological, electrocatalytic oxidation and photocatalytic oxidation have been developed to eliminate phenol, but there are still problems such as high treatment cost, low degradation efficiency and secondary pollution. The electro-Fenton technology in electrocatalytic oxidation has the advantages of high efficiency and simplicity in degrading phenol wastewater. It has been widely studied at home and abroad due to its advantages such as in-situ generation of H2O2 at the cathode and strong oxidation ability.
[0003] However, the traditional electro-Fenton technology realizes the in-situ generation of H2O2 through aeration, which increases the consumption of auxiliary energy. At the same time, electro-Fenton has the disadvantage of metal ion leaching, which limits its practical application. Therefore, the development of a new electro-Fenton cathode, saving aeration costs and reducing metal ion leaching has important scientific significance in the field of sewage treatment.
[0004] In the related prior art, a Chinese invention patent (invention title: A floating natural air diffusion electro-Fenton electrode and a method for treating refractory wastewater, publication number CN116768328A) prepares an electrode with a carbon-based air diffusion layer and a catalyst layer. The electrode is floated on the reaction solution to achieve natural diffusion of oxygen to the electrode, and H2O2 is generated by electrocatalysis and the Fe in the catalyst layer is used to generate H2O2. 2+ Fenton reaction occurs to generate OH to degrade pollutants. Using exogenous metals as catalysts will inevitably lead to secondary pollution caused by metal ion leaching. It is urgent to avoid secondary pollution while saving aeration costs. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to solve the problems existing in the above-mentioned prior art. The present invention aims to provide a nitrogen-doped carbon electro-Fenton breathing cathode and its preparation method and application. The cathode material prepared by the present invention has good application potential in the field of electro-Fenton technology for treating phenol wastewater. It not only saves aeration costs but also avoids the secondary pollution problem caused by metal ion leaching.
[0006] One of the purposes of the present invention is a method for preparing a nitrogen-doped carbon electric Fenton breathing cathode, comprising the following steps: Step 1, pre-treating the surface of the carbon felt substrate by cleaning; Step 2: dispersing a nitrogen-containing precursor substance and graphite in ethanol to obtain a precursor solution; Step 3, adding the concentrated polytetrafluoroethylene dispersion to the precursor solution prepared in step 2 to mix and disperse evenly to obtain a mixed solution; Step 4: evenly coating the mixed solution prepared in step 3 on the carbon felt substrate pretreated in step 1; Step 5: Dry the carbon felt coated in step 4, then calcine it, and then cool it to obtain a nitrogen-doped carbon electrode.
[0007] As a preferred embodiment, in step 1, the carbon felt is placed in ethanol and deionized water respectively for ultrasonic cleaning.
[0008] As a preferred embodiment, in the step 2, the precursor substance is selected from melamine, ammonium nitrate or urea.
[0009] As a preferred embodiment, in the step three, the volume ratio of the added tetrafluoroethylene concentrated dispersion to the ethanol in the step two is 0.003-0.010:1.
[0010] As a preferred embodiment, in the step three, the mass ratio of the added polytetrafluoroethylene concentrated dispersion to the graphite in the step two is 0.65-2.15:1.
[0011] As a preferred embodiment, in the step three, the concentrated polytetrafluoroethylene dispersion is added to the precursor solution prepared in the step two and ultrasonically mixed and dispersed to obtain a mixed solution, and the ultrasonic dispersion time is 10 to 20 minutes.
[0012] As a preferred embodiment, in step 5, the calcination conditions are: heating the temperature in a tube furnace to 300°C to 360°C at a rate of 2°C / min to 10°C / min, and calcining for 30 to 50 min.
[0013] A second object of the present invention is to provide a cathode prepared according to any of the preparation methods described above.
[0014] The third object of the present invention is to provide the use of the cathode described above in the production of H2O2 by electro-Fenton.
[0015] The fourth object of the present invention is to provide an application of the nitrogen-doped carbon breathing cathode material in the electro-Fenton degradation of phenol wastewater, and the application method includes: preparing a phenol solution, taking the electrolyte into a single-chamber reactor, using the nitrogen-doped carbon material as the electro-Fenton cathode, and the reaction is carried out at room temperature.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects: First, the electrode preparation method of the present invention uses CF as the substrate, loads exogenous nitrogen onto the cathode material, and introduces heteroatom nitrogen as the catalytic active site on the surface of the material to activate H2O2 to generate OH to remove pollutants, without the need for additional Fe 2+ And no iron sludge pollution will be generated. By strictly controlling the preparation conditions and calcination process parameters, the entire preparation process is clean and pollution-free, the prepared electrode material has high stability, and can achieve high H2O2 production without aeration. In the absence of exogenous metal addition, nitrogen species are introduced to activate H2O2 to generate ·OH to degrade phenol.
[0017] Secondly, the electrode prepared in this scheme is an electro-Fenton cathode with excellent performance and green environmental protection. It is based on CF, which has the advantages of being cheap and easy to obtain, large specific surface area, excellent conductivity, compact and porous structure, etc. In the electro-Fenton system, without additional aeration, oxygen in the air and oxygen generated by anodic oxidation can be used on the cathode surface through 2e - The oxygen reduction reaction produces H2O2, which provides a new idea for the preparation of cathode materials that produce H2O2 through oxygen reduction.
[0018] Third, the present invention also provides an application of a nitrogen-doped carbon electric Fenton breathing cathode. The electrode material prepared by the preparation method is a highly potential electric Fenton cathode material. The hydrophobic surface of the material prepared by the present invention has a multi-level micro-nano structure that can construct a rich gas-liquid-solid three-phase interface with the reaction solution and oxygen. This scheme vertically immerses the nitrogen-doped carbon breathing cathode into the reaction solution and exposes it at a certain height above the reaction solution, and directly utilizes the oxygen in the air by utilizing the constructed gas-liquid-solid three-phase interface to avoid aeration. The establishment of the three-phase interface can effectively avoid the reaction solution blocking the contact between the solid electrode and the gas. When the super-hydrophobic surface contacts the liquid, an air bag connected to the atmosphere is formed, and the gas is introduced into the reaction interface. The reaction interface of the coexistence of gas, liquid and solid formed on the electrode surface helps to strengthen the mass transfer of oxygen, promote the rapid transmission of oxygen in the air to the surface of the porous carbon material and further reduce it to generate H2O2. The nitrogen-doped carbon electric Fenton breathing cathode prepared by the present invention is used to degrade phenol. The phenol removal rate can reach more than 95% after 180 minutes of reaction, and is close to or even reaches 100% under some conditions, and the degradation application effect is significant. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the SEM image of polytetrafluoroethylene modified carbon felt; Figure 2 This is the SEM image of the electrode material of Example 1; Figure 3 This is the SEM image of the electrode material of Example 2; Figure 4 This is the SEM image of the electrode material of Example 3; Figure 5 Fourier transform infrared spectra of electrode materials prepared with different nitrogen sources in Example 1, Example 2 and Example 3; Figure 6 The figure is a graph showing the degradation effect of the electrode materials prepared in Example 1, Example 2 and Example 3 on phenol; Figure 7 The figure is a graph showing the degradation effect of the electrode materials prepared in Example 1, Example 4 and Example 5 on phenol; Figure 8 A comparison chart of the amount of H2O2 produced by the electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2; Fig. 9 It is a comparison chart of the degradation effects of the electrode materials prepared in CF, Example 1 and Comparative Example 2 on phenol. DETAILED DESCRIPTION
[0020] In order to make the technical means, creative features, objectives and beneficial effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0021] In addition, in order to better illustrate the present invention, numerous specific details are given in the specific embodiments below. Those skilled in the art should understand that the present invention can also be implemented without certain specific details. In other embodiments, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present invention.
[0022] In the present invention, carbon felt is referred to as CF; polytetrafluoroethylene is referred to as PTFE.
[0023] Carbon felt was purchased from Beijing Jinglong Special Carbon Graphite Factory, product number 201.07.00041, thickness 3 mm. Graphite was purchased from Shanghai Huayi Group Huayuan Chemical Co., Ltd. Colloid Chemical Factory; polytetrafluoroethylene concentrated dispersion: 60wt% dispersion, density 2.15 g / mL, McLean, item number P816262. The high performance liquid chromatograph used in the embodiments and comparative examples of this scheme is Dalian Yilite P230II; the infrared lamp is 220 V, power 100 W.
[0024] Unless otherwise specified, the materials and reagents used below can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out according to conventional conditions in the prior art or according to conditions recommended by the manufacturer.
[0025] An embodiment of the present invention provides a method for preparing a nitrogen-doped carbon electric Fenton breathing cathode, comprising the following steps: Step 1, pre-treating the surface of the carbon felt substrate by cleaning; In the step 1, the carbon felt (CF) is placed in ethanol and deionized water respectively for ultrasonic cleaning to remove stains and grease on the original carbon felt.
[0026] Step 2: dispersing a nitrogen-containing precursor substance and graphite in ethanol to obtain a precursor solution; In the step 2, the nitrogen-containing precursor substance is selected from melamine / ammonium nitrate / urea, and the mass ratio of the graphite:precursor substance is 0.5~1:0.5~1.
[0027] Step 3, adding the concentrated polytetrafluoroethylene dispersion to the precursor solution prepared in step 2 to mix and disperse evenly to obtain a mixed solution; Wherein, in the step 3, the volume ratio of the concentrated polytetrafluoroethylene dispersion to ethanol is 0.003-0.01:1, and the mass ratio of the concentrated polytetrafluoroethylene dispersion to graphite is 0.65-2.15:1; preferably, the ultrasonic dispersion time is 10-20 min, more preferably, the ultrasonic dispersion time is 15 min.
[0028] Step 4: evenly apply the mixed solution prepared in step 3 on the carbon felt substrate pretreated in step 1.
[0029] The drying condition in step 4 is drying under infrared light. The mixed solution is evenly applied to the carbon felt one by one and the ethanol is evaporated under infrared light, and the operation is repeated until the solution is completely applied to the carbon felt.
[0030] Step 5: Dry the carbon felt coated in step 4, then calcine it, and then cool it to obtain a nitrogen-doped carbon electrode.
[0031] In the step 5, the calcination conditions are to increase the temperature to 300-360° C. at 2-10° C. / min in a tubular furnace, calcine for 30-50 min, and obtain a nitrogen-doped carbon electrode after cooling.
[0032] Example 1 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0033] Step S2, taking 5 mL of ethanol and placing it in a container, and then ultrasonically dispersing 0.10 g of graphite and 0.10 g of melamine in the ethanol to obtain a precursor solution.
[0034] Step S3, adding 40 μL of the concentrated PTFE dispersion to the precursor solution obtained in step S2 under ultrasonic conditions, and ultrasonically mixing the mixture for 15 min to uniformly disperse the mixture to obtain a dispersion.
[0035] Step S4, uniformly applying the dispersion obtained in step S3 to the CF pretreated in step S1.
[0036] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing the material into a tube furnace, heating it to 360°C at 5°C / min in an Ar atmosphere, calcining it for 40 min, and obtaining a carbon felt-loaded nitrogen-doped carbon breathing electrode after cooling.
[0037] The carbon felt loaded nitrogen-doped carbon breathing electrode prepared in Example 1 was applied and tested by the following method: 0.05 M Na2SO4 was used as the supporting electrolyte, and 60 mL of phenol aqueous solution with an initial concentration of 100 mg / L was added in the degradation experiment. A breathing cathode electro-Fenton system was built, with the electrode immersed in the reaction solution for 2 cm and exposed 1 cm above, and a Pt sheet was used as the anode, and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min, and samples were taken every 30 min. The concentration change of phenol was determined by high performance liquid chromatography (Dalian Yilite P230II). The UV detector wavelength was set to 280 nm, the mobile phase was methanol and pure water (50:50 v / v), and the flow rate was 0.5 mL / min. The H2O2 production was determined by potassium titanium oxalate spectrophotometry. 1 mL of the reaction solution was taken into a colorimetric tube, and 2 mL of 3 mol / L sulfuric acid and 2 mL of 0.05 mol / L potassium titanium oxalate were added in sequence. After being fully shaken and mixed, the mixture was allowed to stand for 10 min, and the absorbance was measured at 400 nm.
[0038] The experimental results show that the electrode has a good removal effect on phenol. After 180 min of reaction, the removal rate of phenol can reach 100%, and the H2O2 production is 7.90 mg / L / cm 2 .
[0039] Example 2 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0040] Step S2, take 5 mL of ethanol and put it in a container, ultrasonically disperse 0.10 g of graphite and 0.10 g of ammonium nitrate in the ethanol to obtain a precursor solution.
[0041] Step S3, adding 40 μL of the concentrated PTFE dispersion to the precursor solution obtained in step S2 under ultrasonic conditions, and ultrasonically mixing the mixture for 15 min to uniformly disperse the mixture to obtain a dispersion.
[0042] Step S4, uniformly applying the dispersion obtained in step S3 to the CF pretreated in step S1.
[0043] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing it in a tube furnace, heating it to 360°C at 5°C / min in an Ar atmosphere and calcining it for 40 min. After cooling, a carbon felt-loaded nitrogen-doped carbon breathing electrode was obtained.
[0044] The carbon felt loaded nitrogen-doped carbon breathing electrode prepared in Example 2 was applied and tested by the following method: 0.05 M Na2SO4 was used as the supporting electrolyte, and 60 mL of phenol aqueous solution with an initial concentration of 100 mg / L was added in the degradation experiment. A breathing cathode electro-Fenton system was built, with the electrode immersed in the reaction solution for 2 cm and exposed 1 cm above, and a Pt sheet was used as the anode, and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min and samples were taken every 30 min. The concentration of phenol was determined by high performance liquid chromatography (Dalian Yilite P230II). The mobile phase was methanol and pure water (50:50 v / v) at a flow rate of 0.5 mL / min. A UV detector was used with a detection wavelength of 280 nm.
[0045] The experimental results show that the electrode material has a good removal effect on phenol, and the removal rate of phenol can reach 96.1% after 180 min of reaction.
[0046] Example 3 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in a certain amount of ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0047] Step S2: 5 mL of ethanol is placed in a container, and 0.10 g of graphite and 0.10 g of urea are ultrasonically dispersed in the ethanol to obtain a precursor solution.
[0048] Step S3, adding 40 μL of the concentrated PTFE dispersion to the precursor solution obtained in step S2 under ultrasonic conditions, and ultrasonically mixing the mixture for 15 min to uniformly disperse the mixture to obtain a dispersion.
[0049] Step S4, uniformly applying the dispersion obtained in step S3 to the CF pretreated in step S1.
[0050] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing the material in a tube furnace, heating it to 360°C at 5°C / min in an Ar atmosphere and calcining it for 40 min. After cooling, a carbon felt-loaded nitrogen-doped carbon breathing electrode was obtained.
[0051] The carbon felt-loaded nitrogen-doped carbon breathing electrode prepared in Example 3 was applied and tested by the following method: 0.05 M Na2SO4 was used as the supporting electrolyte, and 60 mL of phenol with an initial concentration of 100 mg / L was added in the degradation experiment. A breathing cathode electro-Fenton system was built, with the electrode immersed in the reaction solution for 2 cm and exposed 1 cm above, and a Pt sheet was used as the anode, and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min and samples were taken every 30 min. The concentration of phenol was determined by high performance liquid chromatography (Dalian Yilite P230II). The mobile phase was methanol and pure water (50:50 v / v) at a flow rate of 0.5 mL / min. A UV detector was used with a detection wavelength of 280 nm.
[0052] The experimental results show that the electrode has a good removal effect on phenol, and the removal rate of phenol can reach 96.5% after 180 min of reaction.
[0053] Figure 1 This is the SEM image of polytetrafluoroethylene modified carbon felt, showing a uniform rod-like structure and protrusion structure, indicating that polytetrafluoroethylene particles are effectively dispersed on the surface of the carbon felt. Figure 2 , 3 , 4 correspond to the SEM images of Examples 1, 2, and 3, respectively. The nitrogen-doped carbon modifier is in a sheet-like structure attached to the surface of the carbon fiber and wraps it. Polytetrafluoroethylene is attached to the surface of the carbon material and fills the cross-spaces of the carbon felt fibers, proving that the metal-rich nitrogen-doped carbon catalyst is successfully loaded on the electrode matrix.
[0054] The Fourier transform infrared spectra of the electrode materials in Example 1, Example 2 and Example 3 are as follows: Figure 5 As shown in the figure, the characteristic absorption peaks of different electrode materials are similar, and there is no obvious change in the position, intensity and peak shape of the absorption peak. −1 and 3250 cm −1 The peaks between 2750 and 2750 cm belong to the stretching vibrations of NH and OH. The stretching vibration of -OH indicates that the catalyst is rich in oxygen-containing functional groups, which is conducive to the reduction reaction of dissolved oxygen on the electrode surface. The characteristic peak of NH indicates that N is doped into the electrode. The doping of N may cause the electronic structure of the carbon plane to adjust, thereby increasing the catalytic activity. −1 -2850 cm −1 The characteristic peak of the band belongs to CH and is located at 2100 cm−1 The peak that appears nearby is the C≡C characteristic absorption peak.
[0055] Depend on Figure 6 It can be seen that the nitrogen-doped carbon breathing cathodes prepared with melamine, ammonium nitrate and urea as nitrogen sources were used for electro-Fenton degradation of phenol in water, and the reaction time was 180 min, which proved the universality of the preparation method of nitrogen-doped carbon breathing electrodes.
[0056] Example 4 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0057] Step S2, taking 5 mL of ethanol and placing it in a container, and then ultrasonically dispersing 0.10 g of graphite and 0.10 g of melamine in the ethanol to obtain a precursor solution.
[0058] Step S3, adding 40 μL of the concentrated PTFE dispersion to the precursor solution obtained in step S2 under ultrasonic conditions, and ultrasonically mixing the mixture for 15 min to uniformly disperse the mixture to obtain a dispersion.
[0059] Step S4, uniformly applying the dispersion obtained in step S3 to the CF pretreated in step S1.
[0060] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing the material in a tube furnace, heating to 300°C at 5°C / min in an Ar atmosphere, and calcining for 40 min. After cooling, a carbon felt-loaded nitrogen-doped carbon breathing electrode was obtained.
[0061] The carbon felt loaded nitrogen-doped carbon breathing electrode prepared in Example 4 was applied and tested by the following method: 0.05 M Na2SO4 was used as the supporting electrolyte, and 60 mL of phenol aqueous solution with an initial concentration of 100 mg / L was added in the degradation experiment. A breathing cathode electro-Fenton system was built, with the electrode immersed in the reaction solution for 2 cm and exposed above 1 cm. A Pt sheet was used as the anode, and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min and samples were taken every 30 min. The concentration of phenol was determined by high performance liquid chromatography (Dalian Yilite P230II). The mobile phase was methanol and pure water (50:50 v / v) at a flow rate of 0.5 mL / min. A UV detector was used with a detection wavelength of 280 nm.
[0062] The experimental results show that the electrode has a good removal effect on phenol, and the removal rate of phenol can reach 95.3% after 120 min of reaction.
[0063] Example 5 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0064] Step S2, taking 5 mL of ethanol and placing it in a container, and then ultrasonically dispersing 0.10 g of graphite and 0.10 g of melamine in the ethanol to obtain a precursor solution.
[0065] Step S3, adding 40 μL of the concentrated PTFE dispersion to the precursor solution obtained in step S2 under ultrasonic conditions, and ultrasonically mixing the mixture for 15 min to uniformly disperse the mixture to obtain a dispersion.
[0066] Step S4, uniformly applying the dispersion obtained in step S3 to the CF pretreated in step S1.
[0067] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing the material in a tube furnace, heating it to 330°C at 5°C / min in an Ar atmosphere and calcining it for 40 min. After cooling, a carbon felt-loaded nitrogen-doped carbon breathing electrode was obtained.
[0068] The carbon felt-loaded nitrogen-doped carbon breathing electrode prepared in Example 5 was applied and tested by the following method: 0.05 M Na2SO4 was used as the supporting electrolyte, and 60 mL of phenol aqueous solution with an initial concentration of 100 mg / L was added in the degradation experiment. A breathing cathode electro-Fenton system was built, with the electrode immersed in the reaction solution for 2 cm and exposed 1 cm above, and a Pt sheet was used as the anode, and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min, and samples were taken every 30 min. The concentration of phenol was determined by high performance liquid chromatography (Dalian Yilite P230II). The mobile phase was methanol and pure water (50:50 v / v), the flow rate was 0.5 mL / min, and a UV detector was used with a detection wavelength of 280 nm.
[0069] The experimental results show that the electrode has a good removal effect on phenol, and the removal rate of phenol can reach 97.1% after 180 min of reaction.
[0070] Depend on Figure 7It can be seen that the electrode materials in Example 1, Example 4 and Example 5 have good degradation efficiency for phenol. In the process of electrode preparation, in order to prevent the decomposition of polytetrafluoroethylene emulsion to produce toxic gases, the calcination temperature is controlled to be 300-360°C. As the calcination temperature increases, the electrode degradation performance of phenol continues to improve, and the phenol removal rate is the highest when the calcination temperature is 360°C. It is speculated that the molten state of polytetrafluoroethylene changes its microporous structure distribution, thereby affecting the oxygen transport capacity and oxygen reduction performance of the electrode.
[0071] Example 6 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0072] Step S2, taking 10 mL of ethanol and placing it in a container, and then ultrasonically dispersing 0.10 g of graphite and 0.10 g of melamine in the ethanol to obtain a precursor solution.
[0073] Step S3, adding 30 μL of the concentrated PTFE dispersion liquid dropwise to the precursor solution obtained in step S2 under ultrasonic conditions for ultrasonic mixing, and ultrasonicating for 10 min to uniformly disperse the mixed solution to obtain a dispersion liquid.
[0074] Step S4, uniformly applying the dispersion obtained in step S3 to the CF pretreated in step S1.
[0075] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing the material in a tube furnace, heating it to 360°C at 2°C / min in an Ar atmosphere, and calcining it for 30 min. After cooling, a carbon felt-loaded nitrogen-doped carbon breathing electrode was obtained.
[0076] The carbon felt loaded nitrogen-doped carbon breathing electrode prepared in Example 6 was applied and tested by the following method: 0.05 M Na2SO4 was used as the supporting electrolyte, and 60 mL of phenol aqueous solution with an initial concentration of 100 mg / L was added in the degradation experiment. A breathing cathode electro-Fenton system was built, with the electrode immersed 2 cm in the reaction solution and 1 cm exposed above. A Pt sheet was used as the anode, and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min, and samples were taken every 30 min. The concentration of phenol was determined by high performance liquid chromatography. The mobile phase was methanol and pure water (50:50 v / v), the flow rate was 0.5 mL / min, and a UV detector was used with a detection wavelength of 280 nm.
[0077] The experimental results show that the electrode has a good removal effect on phenol, and the removal rate of phenol can reach 93.6% after 180 min of reaction.
[0078] Example 7 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0079] Step S2, take 5 mL of ethanol and put it in a container, then ultrasonically disperse 0.05 g of graphite and 0.10 g of melamine in the ethanol to obtain a precursor solution.
[0080] Step S3, dropwise adding 50 μL of the concentrated PTFE dispersion into the precursor solution obtained in step S2 under ultrasonic conditions for ultrasonic mixing, and ultrasonically mixing for 20 min to uniformly disperse the mixed solution to obtain a dispersion.
[0081] Step S4, uniformly applying the dispersion obtained in step S3 to the CF pretreated in step S1.
[0082] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing the material in a tube furnace, heating it to 360°C at 10°C / min in an Ar atmosphere, and calcining it for 50 min. After cooling, a carbon felt-loaded nitrogen-doped carbon breathing electrode was obtained.
[0083] The carbon felt-loaded nitrogen-doped carbon breathing electrode prepared in Example 7 was applied and tested by the following method: 0.05 M Na2SO4 was used as the supporting electrolyte, and 60 mL of phenol aqueous solution with an initial concentration of 100 mg / L was added in the degradation experiment. A breathing cathode electro-Fenton system was built, with the electrode immersed in the reaction solution for 2 cm and exposed above 1 cm. A Pt sheet was used as the anode, and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min, and samples were taken every 30 min. The concentration of phenol was determined by high performance liquid chromatography. The mobile phase was methanol and pure water (50:50 v / v), the flow rate was 0.5 mL / min, and a UV detector was used with a detection wavelength of 280 nm.
[0084] The experimental results show that the electrode has a good removal effect on phenol, and the removal rate of phenol can reach 92.7% after 180 min of reaction.
[0085] Depressed breathing: Comparative Example 1 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0086] Step S2, taking 5 mL of ethanol and placing it in a container, and then ultrasonically dispersing 0.10 g of graphite and 0.10 g of melamine in the ethanol to obtain a precursor solution.
[0087] Step S3, adding 40 μL of the concentrated PTFE dispersion to the precursor solution obtained in step S2 under ultrasonic conditions, and ultrasonically mixing the mixture for 15 min to uniformly disperse the mixture to obtain a dispersion.
[0088] Step S4, uniformly apply the dispersion prepared in step S3 to the CF pretreated in step S1.
[0089] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing it in a tubular furnace, heating it to 360°C at 5°C / min in an Ar atmosphere and calcining it for 40 min, and obtaining a carbon felt-loaded nitrogen-doped carbon breathing electrode after cooling.
[0090] The carbon felt loaded nitrogen-doped carbon breathing electrode prepared in Comparative Example 1 was applied and tested by the following method: The cooled carbon felt-loaded nitrogen-doped carbon breathing electrode obtained in Comparative Example 1 was coated with a 1 cm wide airtight conductive tape to prevent the electrode from contacting the air above the solution, thereby inhibiting the breathing and utilization of oxygen in the air.
[0091] A breathing cathode electro-Fenton system was constructed using 0.05 M Na2SO4 as the supporting electrolyte. The electrode was immersed in the reaction solution for 2 cm and exposed 1 cm above the surface. A Pt sheet was used as the anode and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min, and samples were taken every 30 min to determine the H2O2 production. The H2O2 production was determined by the potassium titanium oxalate spectrophotometric method in Example 1. 1 mL of the reaction solution was placed in a colorimetric tube, and 2 mL of 3 mol / L sulfuric acid and 2 mL of 0.05 mol / L potassium titanium oxalate were added in sequence. After being fully shaken and mixed, the mixture was allowed to stand for 10 min, and the absorbance was determined at 400 nm.
[0092] The experimental results show that the H2O2 production in Comparative Example 1 reached 5.32 mg / L / cm2 after 180 min of reaction. 2 In Example 1, the H2O2 yield was 7.90 mg / L / cm 2, the H2O2 production in Comparative Example 1 is slightly lower than that in Example 1. The autonomous breathing performance of the electrode in Comparative Example 1 is suppressed, proving that the electrode in Example 1 has breathing performance.
[0093] Without nitrogen source: Comparative Example 2 Step S1, taking a 2 cm×3 cm carbon felt substrate surface for cleaning pretreatment, placing the carbon felt in ethanol for ultrasonic treatment, and then taking it out and performing a second ultrasonic treatment in deionized water, and cleaning the carbon felt through two ultrasonic washings to remove stains and grease on the original carbon felt.
[0094] Step S2, take 5 mL of ethanol and put it in a container, and ultrasonically disperse 0.10 g of graphite in the ethanol to obtain a mixed solution.
[0095] Step S3, adding 40 μL of the concentrated PTFE dispersion to the ethanol mixture in step S2 under ultrasound, and performing ultrasound for 15 min to uniformly disperse the mixture.
[0096] Step S4, uniformly applying the dispersion obtained in step S3 to the CF pretreated in step S1.
[0097] Step S5, drying the electrode prepared in step S4 under an infrared lamp (220 V, power 100 W), then placing the material in a tube furnace, heating to 360°C at 5°C / min in an Ar atmosphere and calcining for 40 min. After cooling, a carbon felt-loaded nitrogen-doped carbon breathing electrode was obtained.
[0098] The carbon felt loaded nitrogen-doped carbon breathing electrode prepared in Comparative Example 2 was applied and tested by the following method: 0.05 M Na2SO4 was used as the supporting electrolyte, and 60 mL of phenol aqueous solution with an initial concentration of 100 mg / L was added in the degradation experiment. A breathing cathode electro-Fenton system was built, with the electrode immersed 2 cm in the reaction solution and 1 cm exposed above. A Pt sheet was used as the anode, and the current density was controlled to be 2.50 mA / cm 2 The reaction was carried out at 25°C for 180 min, and samples were taken every 30 min to determine the H2O2 production and phenol degradation rate. The H2O2 production was determined by the potassium titanium oxalate spectrophotometric method in Example 1. 1 mL of the reaction solution was taken into a colorimetric tube, and 2 mL of 3 mol / L sulfuric acid and 2 mL of 0.05 mol / L potassium titanium oxalate were added in sequence. After being fully shaken and mixed, the mixture was allowed to stand for 10 min, and the absorbance was determined at 400 nm.
[0099] The experimental results show that the H2O2 production in Comparative Example 2 was 47.31 mg / L / cm at 180 min. 2, which is much higher than the H2O2 production in Example 1. However, the phenol degradation rate was 69.1% at 180 min of reaction, which was much lower than that in Example 1. In Comparative Example 2, no exogenous N was introduced, and the generated H2O2 could not be activated to generate ·OH in time, resulting in the accumulation of H2O2; the insufficient generation of ·OH was the reason for the low phenol degradation rate. This further proves that the addition of exogenous N in the example is an active site for catalytic activation of H2O2 to generate ·OH.
[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a nitrogen-doped carbon electric Fenton breathing cathode, characterized in that: The steps include: Step 1, pre-treating the surface of the carbon felt substrate by cleaning; Step 2: dispersing a nitrogen-containing precursor substance and graphite in ethanol to obtain a precursor solution; Step 3, adding the concentrated polytetrafluoroethylene dispersion to the precursor solution prepared in step 2 to mix and disperse evenly to obtain a mixed solution; Step 4: evenly coating the mixed solution prepared in step 3 on the carbon felt substrate pretreated in step 1; Step 5: Dry the carbon felt coated in step 4, then calcine it, and then cool it to obtain a nitrogen-doped carbon electrode.
2. The method for preparing a nitrogen-doped carbon electric Fenton breathing cathode according to claim 1, characterized in that: In the step 1, the carbon felt is placed in ethanol and deionized water respectively for ultrasonic cleaning.
3. The method for preparing a nitrogen-doped carbon electric Fenton breathing cathode according to claim 1, characterized in that: In the step 2, the precursor substance is selected from melamine, ammonium nitrate or urea.
4. The method for preparing a nitrogen-doped carbon electric Fenton breathing cathode according to claim 1, characterized in that: In the step 3, the volume ratio of the added tetrafluoroethylene concentrated dispersion to the ethanol in the step 2 is 0.003-0.010:
1.
5. The method for preparing a nitrogen-doped carbon electric Fenton breathing cathode according to claim 1, characterized in that: In the step 3, the mass ratio of the added polytetrafluoroethylene concentrated dispersion to the graphite in the step 2 is 0.65-2.15:
1.
6. The method for preparing a nitrogen-doped carbon electric Fenton breathing cathode according to claim 1, characterized in that: In the step three, the concentrated polytetrafluoroethylene dispersion is added to the precursor solution prepared in the step two and ultrasonically mixed and dispersed to obtain a mixed solution. The ultrasonic dispersion time is 10 to 20 minutes.
7. The method for preparing a nitrogen-doped carbon electric Fenton breathing cathode according to claim 1, characterized in that: In the step 5, the calcination conditions are: heating the temperature in a tubular furnace to 300° C. to 360° C. at a rate of 2° C. / min to 10° C. / min, and calcining for 30 to 50 min.
8. A cathode prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the cathode according to claim 8 in producing H2O2 by electro-Fenton.
10. The use of the cathode in degrading phenol wastewater according to claim 8, characterized in that: The application method comprises the following steps: preparing a phenol solution, taking an electrolyte into a single-chamber reactor, using a nitrogen-doped carbon material as an electro-Fenton cathode, and performing a reaction at room temperature.
Citation Information
Patent Citations
Floating type natural air diffusion electro-Fenton electrode and method for treating refractory sewage
CN116768328A
Preparation method for high-catalytic activity nitrogen-doped graphene composite cathode and organic pollutant degrading technology
CN107739074A
Cited By
Boron-nitrogen co-doped porous carbon self-breathing electrode and application thereof in construction of self-breathing heterogeneous electro-Fenton system
CN121626968A
